Get Answers to all your Questions

header-bg qa
Filter By

All Questions

If the height of a tower and the distance of the point of observation from its foot, both, are increased by 10%, then the angle of elevation of its top remains unchanged.

According to question


In case-1. Height is H and observation distance is A.
In case 2, both height and observation distance are increased by 10%.
In case -1
\tan \theta _{1}= \frac{H}{a}         \left ( \because \tan \theta = \frac{perpendicular}{Base} \right )  .....(1)
In case -2
\tan \theta _{2}= \frac{H+\frac{H}{10}}{a+\frac{a}{10}}
= \frac{\frac{11H}{10}}{\frac{11a}{10}}= \frac{11H}{10}\times \frac{10}{11a}= \frac{H}{a}
\tan \theta _{2}= \frac{H}{a} \cdots \left ( 2 \right )
from equation (1) and (2) we observe that \theta _{1}= \theta _{2}
Hence the given statement is true.

View Full Answer(1)
Posted by

infoexpert27

The angle of elevation of the top of a tower is 30°. If the height of the tower is doubled, then the angle of elevation of its top will also be doubled.

According to question

Case: 1
Here BC is the tower.
Let the height of the tower be H and distance AB = a
In 
\bigtriangleup
ABC

 \tan\theta=\frac{Perpendicular}{Base}

\tan 30^{\circ}= \frac{H}{a}           \left ( \because \theta = 30^{\circ} \right )      

\frac{1}{\sqrt{3}}= \frac{H}{a}\; \cdots \left ( 1 \right )       \left ( \because \tan 30^{\circ} = \frac{1}{\sqrt{3}}\right )                    

Case:2    When height is doubled

Here ED = a
In \bigtriangleup DEF
\tan \theta = \frac{2H}{a}
\tan \theta = \frac{2}{3}   (from (1))
But \tan 60^{\circ}= \sqrt{3}         (If the angle is double)
\sqrt{3}\neq \frac{2}{\sqrt{3}}
Hence the given statement is false.                 

View Full Answer(1)
Posted by

infoexpert27

Crack CUET with india's "Best Teachers"

  • HD Video Lectures
  • Unlimited Mock Tests
  • Faculty Support
cuet_ads

\cos \theta = \frac{a^{2}+b^{2}}{2ab} where a and b are two distinct numbers such that ab> 0.

We know that

-1\leq \cos \theta \leq 1
We also know that

\left ( a-b \right )^{2}= a^{2}+b^{2}-2ab
\text{Since }  \left ( a-b \right )^{2} \text{is a square term hence it is always positive }
\left ( a-b \right )^{2}> 0
a2 + b2 – 2ab > 0
a^{2}+b^{2}> 2ab
We observe that a^{2}+b^{2} is always greater than 2ab.
Hence,         

  \frac{a^{2}+b^{2}}{2ab}> 1
Because if we divide a big term by small then the result is always greater than 1.
cos\theta is always less than or equal to 1
Hence the given statement is false.

View Full Answer(1)
Posted by

infoexpert27

The value of 2sinθ can be a+1/a , where a is a positive number, and a ≠ 1.

Answer.       [False]            
Solution.    We know that
  -1≤ sin θ ≤ 1
Multiply by 2.
-2≤ 2 sin θ ≤ 2
Here we found that value of 2 sin \theta is lies from – 2 to 2.
But if we take a > 0 and a \neq 1 then
a+\frac{1}{a}> 2
For example a = 3
3 + 1/3 = 3.33
Hence a+\frac{1}{a} is always greater than 2 in case of positive number except 1
But value of 2 sin \theta  is not greater than 2
Hence the given statement is false

View Full Answer(1)
Posted by

infoexpert27

JEE Main high-scoring chapters and topics

Study 40% syllabus and score up to 100% marks in JEE

If a man standing on a platform 3 metres above the surface of a lake observes a cloud and its reflection in the lake, then the angle of elevation of the cloud is equal to the angle of depression of its reflection.

According to the question.

In the figure \theta _{1} is the angle of elevation and \theta _{2} the angle of depression of the cloud.
For finding \theta _{1}find tan value in \bigtriangleupECD
\tan \theta _{1}= \frac{perpendicular}{Base}= \frac{DC}{EC}= \frac{H}{\iota }
Find tan\theta in \bigtriangleupECB for \theta _{2}
\tan \theta _{2}= \frac{BC}{EC}= \frac{3}{\iota }
Here we found that \theta _{1} and \theta _{2} both are different.
Hence the given statement is false.

View Full Answer(1)
Posted by

infoexpert27

Write ‘True’ or ‘False’ and justify your answer in each of the following:

If the length of the shadow of a tower is increasing, then the angle of elevation of the sun is also increasing.

Case 1:

Case 2 :

\theta _{1} Is the angle when the length is small and \theta _{2} is the angle when shadow length is increased.
For finding \theta _{1}, \theta _{2} find tan \theta

\tan \theta_{1} = \frac{Perpendicular}{Base}= \frac{height\, of\, tower}{length\, of\, shadow}
\tan \theta_{2} = \frac{height\, of\, tower}{length\, of\, shadow}
In both the case height of the tower is the same but in case 2 length of the shadow is increased and if the length of the shadow increases value  \theta _{2} decreases.
Hence the given statement is false.

View Full Answer(1)
Posted by

infoexpert27

NEET 2024 Most scoring concepts

    Just Study 32% of the NEET syllabus and Score up to 100% marks


(tanθ + 2) (2 tan θ + 1) = 5 tan θ + sec2θ.

 (tanθ + 2) (2 tan θ + 1) = 5 tan θ + sec2θ
Taking L.H.S.
(tanθ + 2) (2 tan θ + 1) 
tanθ.(2tan θ+1) + 2(2tan θ +1)
2\tan ^{2}\theta +\tan \theta +4\tan \theta+2
2\tan ^{2}\theta +5\tan \theta+2
2\left ( \tan ^{2}\theta +1 \right )+5\tan \theta\: \cdots \left ( 1 \right )
We know that

\sec ^{2 }\theta-\tan ^{2}\theta= 1
\left ( 1+\tan ^{2}\theta= \sec ^{2}\theta \right )  

Put the above value in (1)we get
2\sec ^{2}\theta +5\tan \theta \neq 5\tan \theta +\sec ^{2}\theta
L.H.S. \neq R.H.S.
Hence the given expression is false.

 

 

View Full Answer(1)
Posted by

infoexpert27

If cosA + cos2A = 1, then sin2A + sin4A = 1.

Given
cosA + cos2A = 1        …(1) 
cos A = 1 – cos2A
cosA = sin2A          …(2)    (\because sin2 \theta = 1 – cos2\theta)
\sin ^{2} A+\sin ^{4}A= 1
L.H.S.

\sin ^{2} A+\sin ^{4}A
\sin ^{2} A+ \left ( \sin ^{2}A \right )^{2}
 \cos A+\left ( \cos A \right )^{2} (from (2))
cosA + cos2A
= 1       (R.H.S.)           (from (1))
Hence sin2A + sin4A = 1
So, the given statement is true.

View Full Answer(1)
Posted by

infoexpert27

Crack CUET with india's "Best Teachers"

  • HD Video Lectures
  • Unlimited Mock Tests
  • Faculty Support
cuet_ads

Prove that \sqrt{\left ( 1-\cos ^{2}\theta \right )\sec ^{2}\theta }= \tan \theta

   
L.H.S

 \sqrt{\left ( 1-\cos ^{2}\theta \right )\sec ^{2}\theta } \cdots \left ( 1 \right )
   We know that
1-\cos ^{2}\theta = \sin ^{2}\theta\text{ in (1)}
\sqrt{\sin ^{2}\theta \cdot \sec ^{2}\theta }
=\sqrt{\sin ^{2}\theta \times \frac{1}{\cos ^{2}\theta } }             \left ( \because \sec \theta = \frac{1}{\cos \theta } \right )
=\sqrt{\frac{\sin ^{2}\theta }{\cos ^{2}\theta }}
=\sqrt{\tan ^{2}\theta }= \tan \theta                   \left ( \because \frac{\sin \theta }{\cos \theta }= \tan \theta \right )

L.H.S. = R.H.S.

Hence the given expression is true.

 

View Full Answer(1)
Posted by

infoexpert27

The value of the expression (sin 80° – cos80°) is negative.

Answer.     [False]
Solution.     (sin 80° – cos 80°)
We know that from 0 to 90° sin\theta  and cos\theta  both are positive i.e.
0< \sin \theta \leq 90^{\circ}  (always positive)
 0< \cos \theta \leq 90^{\circ} (always positive)
At 45° both the values of sin\theta  and cos\theta  are the same but after 45° to 90° value of sin is greater than the value of cos\theta Hence sin 80° > cos 80°.
If we subtract a smaller term from bigger than the result is positive.
Hence (sin 80° – cos80°) > 0
So, the given statement is false

View Full Answer(1)
Posted by

infoexpert27

JEE Main high-scoring chapters and topics

Study 40% syllabus and score up to 100% marks in JEE

filter_img